Proton beam radiation therapy vs. photon radiation therapy and the overall survival of adult and pediatric patients diagnosed with sarcoma - Amin, Saber A.; Mateen, Zubair A.; Amin, Palwasha; Lin, Chi (Frontiers in Oncology, 2025)
BackgroundThe use of proton beam radiation therapy (PBT) has increased in patients diagnosed with sarcoma. However, there is a lack of information about its survival benefit in these patients.ObjectiveWe want to investigate the association of PBT with the overall survival (OS) of sarcoma patients.MethodsWe used the National Cancer Database and assessed the OS using multivariable Cox regression analysis adjusted for age, sex, race, education, income, insurance status, histology, comorbidity score, radiation therapy dose, chemotherapy, surgery, and year of diagnosis.ResultsAmong the 117,694 patients, 3,573 (3%) received PBT. Patients receiving PBT had longer OS than those receiving photon radiation therapy (PRT) (HR: 0.73, CI: 0.68 -0.79). PBT was also associated with improved OS compared to PRT in chordoma (HR: 0.57, CI: 0.44-0.74), rhabdomyosarcoma (HR: 0.58, 95% CI: 0.47- 0.72), or chondrosarcoma (HR: 0.35, CI: 0.24-0.51) patients. Among patients who received surgery, PBT was associated with improved OS compared to PRT in chordoma (HR: 0.37, CI: 0.22-0.60), chondrosarcoma (HR: 0.52, CI: 0.28-0.97), or osteosarcoma (HR: 0.32, CI: 0.12-0.89) patients. Among patients with no surgery, PBT was associated with improved OS compared to PRT in chordoma (HR: 0.57, CI: 0.44-0.74), rhabdomyosarcoma (HR:0.56, CI: 0.44-0.70), chondrosarcoma (HR:0.24, CI: 0.15-0.37), osteosarcoma (HR: 0.51, CI: 0.30- 0.87), or other histology type (HR:0.76, CI: 0.66-0.86) patients.ConclusionThe use of PBT was associated with improved OS compared to photon RT in sarcoma patients. PBT was associated with improved OS in patients diagnosed with chordoma, rhabdomyosarcoma, or chondrosarcoma.